Operando Neutron Depth Profiling to Determine the Spatial Distribution of Li in Li-ion Batteries - Verhallen, Tomas W.; Lv, Shasha; Wagemaker, Marnix (Frontiers in Energy Research, 2018)
Neutron Depth Profiling allows determination of the spatial distribution of specific isotopes, via neutron capture reactions. In a capture reaction charged particles with fixed kinetic energy are formed, where their energy loss through the material of interest can be used to provide the depth of the original isotope. As lithium-6 has a relatively large probability for such a capture reaction, it can be used by battery scientists to study the lithium concentration in the electrodes even during battery operation. The selective measurement of the 6Li isotope makes it a direct and sensitive technique, whereas the penetrative character of the neutrons allows practical battery pouch cells to be studied. Using neutron depth profiling lithium diffusion and reaction rates can be studied operando as a function of depth, opening a large range of opportunities including the study of alloying reactions, metal plating and (de) intercalation in insertion hosts. In the study of high rate cycling of intercalation materials the relatively low Li density challenges counting statistics while the limited change in electrode density due to the Li-ion insertion and extraction allows straightforward determination of the Li density as a function of electrode depth. If an electrode can be (dis)charged reversibly, data can be acquired and accumulated over multiple cycles to increase the time resolution. For Li metal plating and alloying reactions, the large lithium density allows good time resolution, however the large change of the electrode composition and density makes extracting the Li-density as a function of depth more challenging. Here an effective method is presented, using calibration measurements of the individual components, based on which the ratio of the components as a function of depth can be determined as well as the total Li-density. The same principles can be applied to insertion host materials, where the differences in density due to electrolyte infiltration yield the electrode porosity as a function of depth. This is of particular importance for battery electrodes where porosity has a direct influence on the energy density and charge transport.